Artificial magnetism for a harmonically trapped Fermi gas in a synthetic magnetic field. (28th June 2023) - Biswas, Shyamal; Ghosh, Avijit; Majumder, Soumyadeep
Abstract: We have analytically explored the artificial magnetism for a 3D spin-polarized harmonically trapped ideal Fermi gas of electrically neutral particles exposed to a uniform synthetic magnetic field. Though polarization of the spin is necessary for trapping electrically neutral atoms in a magneto-optical trap, Pauli paramagnetism can not be studied for the spin-polarized Fermi system. However, it is possible to study Landau diamagnetism and de Haas-van Alphen effect for such a system. We have unified the artificial Landau diamagnetism and the artificial de Haas-van Alphen effect in a single framework for all temperatures as well as for all possible magnitudes of the synthetic magnetic field in the thermodynamic limit. Our prediction is testable in the present-day experimental setup for ultracold fermionic atoms in magneto-optical trap.